2014
DOI: 10.17221/238/2013-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Identification and classification of bulk paddy, brown, and white rice cultivars with colour features extraction using image analysis and neural network

Abstract: Golpour I., Parian J.A., Chayjan R.A. (2014): Identification and classification of bulk paddy, brown, and white rice cultivars with colour features extraction using image analysis and neural network. Czech J. Food Sci., 32: 280-287.We identify five rice cultivars by mean of developing an image processing algorithm. After preprocessing operations, 36 colour features in RGB, HSI, HSV spaces were extracted from the images. These 36 colour features were used as inputs in back propagation neural network. The featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…Classifications of different varieties of seed were also carried out during the past few years using different classification models. Various classification models based on bulk grain samples were reported in [1,2,12,18,25,37]. It is observed that the classification tasks involved in the above literature were not challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Classifications of different varieties of seed were also carried out during the past few years using different classification models. Various classification models based on bulk grain samples were reported in [1,2,12,18,25,37]. It is observed that the classification tasks involved in the above literature were not challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Iman Golpour et.al and S.Majumdar et.al. suggested STEPDISC analysis method for feature selection [18], [19]. Anami et.al projected feature extraction methods for identification and classification of food grains, fruits and flowers [20].…”
Section: Introductionmentioning
confidence: 99%
“…Then, by means of principal component analysis, the structure of the wavelet textural features was determined and finally classification ratio of 96.82% for different types of Chinese famous tea using multi-class least square support vector machine could be found. Golpour et al [14] tried to identify five rice cultivars by means of developing an image processing algorithm. Thirteen color features were applied and a 96.66% classification accuracy using an optimized neural network with two hidden layers was achieved.…”
Section: Introductionmentioning
confidence: 99%